Mathematics (2018) | Study Mode

Join Discuss Share Question Share to WhatsApp
Question 33
A
N828.00 
B
N756.00 
C
N720.00 
D
N684.00 
Explanation.
Share Answer

Since the salary increases by 36 after every 6 months

Every 6 months that can be counted on the eight month of the third year is 5

(i.e. 2 times in the first year, 2 times in the second year and once in the third year)

His salary then = initial salary + increment

= 540 + 5(36)

= 540 + 180

= ?720.00

It can also be solves using a sequence in form of an AP

Answer is C


Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 34
A
52cm 
B
43cm 
C
40cm 
D
15cm 
Explanation.
Share Answer

Tan 74 = 150/x

x = 150/tan 74

= 43.01cm


Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 36
A
72 
B
144 
C
360 
D
720 
Explanation.
Share Answer

The word LEADER has 1L 2E 1A 1D and 1R making total of 6! \(\frac{6}{1!2!1!1!1!}\) = \(\frac{6!}{2!}\)

= \(\frac{6 \times 5 \times 4 \times 3 \times 2 \times 1}{2 \times 1}\)

= 360


Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 37
A
32cm 
B
24 cm 
C
16 cm 
D
12 cm 
Explanation.
Share Answer

From the figure,

XMN = XZY

Angle X is common

So, XNM = XYZ

Then from the angle relationship

\(\frac{XM}{XZ}\) = \(\frac{XN}{XY}\) = \(\frac{MN}{ZY}\)

XM = 8, XZ = 12 + 4 = 16,

XN = 12, XY = 8 + YM

\(\frac{8}{16}\) = \(\frac{12}{(8 +YM) }\)

Cross multiply

8(8 + YM) = 192

64 + 8YM = 192

8YM = 128

YM = \(\frac{128}{8}\)

= 16cm


Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 38
A
3% 
B
3 \(\frac{1}{3}\)% 
C
15% 
D
30% 
Explanation.
Share Answer

The two numbers must be expressed in the same unit. To convert 495g to kg, it will be divided by 1000

495g = \(\frac{495}{1000}\)

= 0.495kg

To express in percentage, 0.495 will be divided by 16.5 and then multiplied by 100

% will be added to the answer \(\frac{0.4950}{16.5}\) x 100

= 3%


Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 40
A
y = 2x - 4 
B
y = 2x + 4 
C
y = 2x - 2 
D
y = 2x + 2 
Explanation.
Share Answer

The gradient to the curve is found by differentiating the curve equation with respect to x

So \(\frac{dy}{dx}\) 2x - 2

The gradient of the curve is the same with that of the tangent.

At point (2, 0) \(\frac{dy}{dx}\) = 2(2) - 2

= 4 2 = 2

The equation of the tangent is given by (y - y1) \(\frac{dy}{dx}\) (x x1)

At point (x1, y1) = (2, 0)

y - 0 = 2(x - 2)

y = 2x - 4


Correct Option:
A
Previous Page Next Page
Question Map
Quiz link
Share Mathematics (2018) with your friends
Share to WhatsApp Share Quiz CBT mode Study mode copy link